A Trace of Crime (a Keri Locke Mystery--Book #4) - Blake, Pierce (Lukeman Literary, 2017)
"A dynamic story line that grips from the first chapter and doesn't let go." --Midwest Book Review, Diane Donovan (regarding Once Gone) From #1 bestselling mystery author Blake Pierce comes a new masterpiece of psychological suspense. In A TRACE OF CRIME (Book #4 in the Keri Locke mystery series), Keri Locke, Missing Persons Detective in the Homicide division of the LAPD, follows a fresh lead for her abducted daughter. She winds her way through a twisted underworld, and step by step, she gets closer to finding her daughter. Yet she has no time. Keri is assigned a new case: a dad calls from an affluent community and reports that his teen daughter vanished on the way home from school. Shortly after, ransom letters arrive. Twisted, filled with riddles, they make it clear that there is little time to save the girl. They also make it clear that this is the work of a diabolical killer who is toying with them. Keri and the police must scramble to find the kidnapper, to understand his demands, to decode the letters, and most of all, to outwit him. But in this master game of chess, Keri may find herself up against a foe even she cannot understand, and for the missing girl-and her own daughter-she may just be too late. A dark psychological thriller with heart-pounding suspense, A TRACE OF CRIME is book #4 in a riveting new series-and a beloved new character-that will leave you turning pages late into the night. "A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) Book #5 in the Keri Locke series will be available soon.
Keywords: Krimi, detektivky